Penerapan Gaya Retro Pada Desain Interior Cyber Net And Bar - Irwansyah Irwansyah; Rindi Novilia Yolanda; Khairani Puspita (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In Indonesia, public awareness of the Internet has grown very rapidly. Especially for students, teachers and other communities. Technology is present and has become part of human life, as if someone cannot work without smartphones, tablets and computers which are production tools for modern technology. Apart from that, the increasing popularity of the Internet among the public has led to the proliferation of internet cafe businesses in several cities in Indonesia. , one of which is Medan City. Cyber ​​Net is a place that facilitates people in using the internet as a medium for playing online games as well as a medium for seeking information and learning. The aim of the research was to create a comfortable gaming place that would attract the attention of e-sports users. By using a qualitative approach, it is hoped that this research can produce a design that not only pays attention to beauty and aesthetic aspects, but also pays attention to the appropriate and comfortable position and layout.